A Comparative Study of Experimental and Theoretical Ultrasonic Velocity of Binary Liquid Mixtures Using Mathematical Methods - Gayathri, A.; Venugopal, T.; Venkatramanan, K. (International Journal of Engineering and Technology, 2018)
A comparative study of ultrasonic velocities of binary liquid mixtures such as O-cresol+carbon tetrachloride, anisicaldehyde+methylacetate, anisicaldehyde+ethylacetate, having industrial applications are analysed at temperature 303K for different concentrations [0 to 1%]. In the present study experimental values are taken from literature and there values are compared with theoretical values obtained by various mathematical equations such as Nomotoâ€™s relation, VandealVangeal formula, Impedance relation, Raoâ€™s specific relation. Thus, the present study reveals the nature of interaction between component molecules in the mixtures and enables us to identify a suitable mathematical model for predicting the ultrasonic velocity various binary liquid mixtures.Â Â Â